Non‐Volatile Resistive Switching in Nanoscaled Elemental Tellurium by Vapor Transport Deposition on Gold - Sara Ghomi; Christian Martella; Yoonseok Lee; Penny Hui‐Ping Chang; Paolo Targa; Andrea Serafini; Davide Codegoni; Chiara Massetti; Sepideh Gharedaghi; Alessio Lamperti; Carlo Grazianetti; Deji Akinwande; et al. (Advanced Science)
Abstract Two‐dimensional (2D) materials are promising for resistive switching in neuromorphic and in‐memory computing, as their atomic thickness substantially improve the energetic budget of the device and circuits. However, many 2D resistive switching materials struggle with complex growth methods or limited scalability. 2D tellurium exhibits striking characteristics such as simplicity in chemistry, structure, and synthesis making it suitable for various applications. This study reports the first memristor design based on nanoscaled tellurium synthesized by vapor transport deposition (VTD) at a temperature as low as 100 °C fully compatible with back‐end‐of‐line processing. The resistive switching behavior of tellurium nanosheets is studied by conductive atomic force microscopy, providing valuable insights into its memristive functionality, supported by microscale device measurements. Selecting gold as the substrate material enhances the memristive behavior of nanoscaled tellurium in terms of reduced values of set voltage and energy consumption. In addition, formation of conductive paths leading to resistive switching behavior on the gold substrate is driven by gold‐tellurium interface reconfiguration during the VTD process as revealed by energy electron loss spectroscopy analysis. These findings reveal the potential of nanoscaled tellurium as a versatile and scalable material for neuromorphic computing and underscore the influential role of gold electrodes in enhancing its memristive performance.